2022
DOI: 10.3390/w14142151
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Periphytic Algal Community and Its Relationship with Environmental Factors in the Taiyuan Region of the Fenhe River

Abstract: In order to explore the characteristics of the periphytic algae community structure and its relationship with environmental factors in the Taiyuan region of the Fenhe River, a total of six sampling sites were investigated in July and December 2021. The effects of water quality status and environmental factors at each sampling point on the community structure of epiphytes were detected. The results showed that a total of 7 phyla and 54 genera of periphytic algae were identified in the Taiyuan region of the Fenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…IN was the most important environmental factor affecting the structure of the bacterial community in the benthic-culture area. Some environmental factors are limiting factors in a certain period of time, but their limitations also change with seasons and times [49]. H. Zhang et al [50]NH + 4 -N and TN were found to be the main factors forming water microbial communities in shrimp aquaculture ecosystems.…”
Section: Effects Of Environmental Factors On Bacterial Community Stru...mentioning
confidence: 99%
“…IN was the most important environmental factor affecting the structure of the bacterial community in the benthic-culture area. Some environmental factors are limiting factors in a certain period of time, but their limitations also change with seasons and times [49]. H. Zhang et al [50]NH + 4 -N and TN were found to be the main factors forming water microbial communities in shrimp aquaculture ecosystems.…”
Section: Effects Of Environmental Factors On Bacterial Community Stru...mentioning
confidence: 99%
“…Temperature is an emerging stressor aggravated by climate change, causing both physiological stress and indirectly affecting oxygen concentrations and thereby invertebrates and fish (Frakes et al, 2021;Jonsson and Jonsson, 2009;Reid et al, 2019). Substrate type and flow velocity strongly shape riverine communities via habitat provision, and their modification leads to a general biodiversity decline (Biggs, 1996;Death and Winterbourn, 1995;Hoyle et al, 2017), while nutrients particularly influence bacteria, benthic and periphytic algae (Hering et al, 2006;Kinsman-Costello et al, 2023;Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%